Relationship between ball release point variability and pitching performance in major league baseball - Wakamiya, Kazuki; Nagamoto, Hideaki; Yamaguchi, Ryusei; Okunuki, Takumi; Maemichi, Toshihiro; Liu, Zijian; Ogawa, Yuki; Kobayashi, Yusuke; Kumai, Tsukasa (Frontiers in Sports and Active Living, 2024)
This study investigated the relationship between ball release points and pitching performance among professional baseball pitchers. Focusing particularly on ball release point variability, we used open-source data to compare ball release point variability between Major League Baseball (MLB) and Minor League Baseball (MiLB) players, and compared the relationship between pitching performance and variability. The relationship between pitching performance and variability was analyzed. MLB players had smaller ball release point variability than MiLB players, and multiple regression analysis showed that pitching performance was strongly related to ball release point variability, especially in the horizontal direction on the coronal plane . Furthermore, horizontal ball release point variability was most strongly related to strikeout ability among pitching performances. These results suggest that reducing horizontal ball release point variability may improve pitching performance, particularly by increasing strikeout and reducing home run allowed. These results are expected to contribute to future pitcher development. This study provides a data-driven approach to understanding the mechanics of pitching and can be applied to the development of advanced training methods and technical solutions aimed at improving pitching performance in baseball players.